John Heartfield’s Photomontages as a Political Tool - Arslan, Doğan (European Journal of Multidisciplinary Studies, 2018)
It is the fact that art often involves with politics. It can work both of sides, either with a political ideology or against of it. The strong relationship between art and politic was occurred during the World War I and World War II. As a member of Berlin Dadaist Art Movement, John Heartfield made sharp opposition with his photomontage works against the Hitler regime in Germany. Since photomontage became anti-art technique against traditional painting in Dada Movement, Heartfield used this technique to criticize his opponents, Adolph Hitler and Mussolini. This research will focus on how Heartfield attacked and disrupted with his photomontages to his opponents. Later on, I will analyze photomontages of Peter Kennard and Klaus Staeck, contemporary artists and designers, who were inspired by Heartfield’s photomontage methodology and his artistic activism. The qualitative research and comparative methodology were used in this research. The findings of the research showed that Heartfield became the pioneer of using photomontage technique in his time. He realized that he could use photography to express his politic thoughts and ideas in collage making. He used photomontage as a political weapon against his political oppositions. Kennard and Staeck, like Heartfield, used photomontage to support and defend their political issues in their time, too. Finannly, this research shows that Dada artist, John Heartfield as well as contemporaray designer and artist Peter Kennard and Klaus Staeck used the photomontage to make a social criticism through their conceptual and powerful works. Their initial approaches were not making design for a client or gallery to sell their works, but they wanted to be, as “artists-activists”, part of social changes in their time.